Chlamydial and gonococcal antibodies in sera of infertile women with tubal obstruction. Issue 4 (April 1987) - Robertson, J N; Ward, M E; Conway, D; Caul, E O
Abstract : Sera from 48 infertile women with tubal pathology and from 77 infertile women with normal fallopian tubes were tested by enzyme linked immunosorbent assay (ELISA) using Chlamydia trachomatis and Neisseria gonorrhoeae antigens. Control sera were obtained from women undergoing abortion, sterilisation, and from women practising barrier contraception. The results of ELISA for antibodies to chlamydiae were in close agreement with results published previously of an immunofluorescence test on these sera. Antibodies to C trachomatis were found in 73% of the infertile women with tubal pathology, significantly more than in any of the control groups. Only a very low prevalence (2-5%) of antibodies to gonococcal pili was found in all groups, except women undergoing abortion (16%).